The influence of lumbar spinal drainage on diffusion parameters in patients with suspected normal pressure hydrocephalus using 3T MRI. (June 2014) - Reiss-Zimmermann, Martin; Scheel, Michael; Dengl, Markus; Preuß, Matthias; Fritzsch, Dominik; Hoffmann, Karl-Titus
Background: Normal pressure hydrocephalus (NPH) has been an ongoing and challenging field of research for the past decades because two main issues are still not fully understood: the pathophysiologic mechanisms underlying ventricular enlargement and prediction of outcome after surgery. Purpose: To evaluate changes in diffusion tensor imaging (DTI) derived parameters in patients with suspected normal pressure hydrocephalus before and after withdrawal of cerebrospinal fluid (CSF). Material and Methods: Twenty-four consecutive patients with clinical and radiological suspicion of NPH and 14 age-matched control subjects were examined with DTI on a clinical 3T scanner. Patients were examined before and 6–36 h after CSF drainage (interval between scans, 5 days). Fifteen patients were finally included in data analysis. Fractional anisotropy (FA) and mean, parallel, and radial diffusivity (MD, PD, RD) were evaluated using a combination of a ROI-based approach and a whole-brain voxel-by-voxel analysis. Results: Alteration of DTI parameters in patients with suspected NPH is regionally different. Compared to the control group, we found an elevation of FA in the subcortical white matter (SCWM) and corpus callosum, whereas the other diffusion parameters showed an increase throughout the brain in variable extent. We also found a slight normalization of RD in the SCWM in patients after lumbar drainage. Conclusion: Our results show that DWI parameters are regionally dependent and reflect multifactorial (patho-) physiological mechanisms, which need to be interpreted carefully. It seems that improvement of gait is caused by a decrease of interstitial water deposition in the SCWM.